Nationwide implementation of online communication skills training to reduce overprescribing of antibiotics: a stepped-wedge cluster randomized trial in general practice. Issue 3 (29th June 2022) - D'Hulster, Leon; Abrams, Steven; Bruyndonckx, Robin; Anthierens, Sibyl; Adriaenssens, Niels; Butler, Chris C; Verheij, Theo; Goossens, Herman; Little, Paul; Coenen, Samuel
Abstract: Objectives: Primary care is responsible for a large proportion of unnecessary antibiotic use, which is one of the main drivers of antibiotic resistance. Randomized trials have found that online communication skills training for GPs reduces antibiotic prescribing for respiratory infections. This study assesses the real-world effect of implementing online communication skills training in general practice. Methods: In a closed cohort stepped-wedge cluster randomized trial all Belgian GPs were invited to participate in online communication skills training courses (TRACE and INTRO) and provided with linked patient information booklets. The primary outcome was the antibiotic prescribing rate per 1000 patient contacts. Intention-to-treat and per protocol analyses were performed. Trial registration at ClinicalTrials.gov: NCT03265028. Results: In total, 118 487 observations from 10 375 GPs were included in the analysis. Overall, 299 (2.88%) GPs completed TRACE and 93 (0.90%) completed INTRO, 30 of which completed both. There was no effect of the national implementation of TRACE and INTRO on the population-level antibiotic prescribing rate (prescribing rate ratio [PRR] = 0.99 [95% CI: 0.97–1.02]). GPs who actually completed TRACE prescribed fewer antibiotic prescriptions (PRR = 0.93 [95% CI: 0.90–0.95]). Conclusions: Inviting GPs to complete an online communication skills training course and providing them with the linked patient information booklets did not reduce antibiotic prescribing. However, GPs who completed TRACE prescribed 7% fewer antibiotics, especially during winter. This suggests a significant decrease in population-wide antibiotic consumption could be achieved by focusing on increasing the uptake of this intervention by identifying and overcoming barriers to participation.